Antihypertensive Therapy by ACEI/ARB Is Associated With Intestinal Flora Alterations and Metabolomic Profiles in Hypertensive Patients - Dong, Ying; Wang, Pan; Jiao, Jie; Yang, Xinchun; Chen, Mulei; Li, Jing (Frontiers in Cell and Developmental Biology, 2022)
Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers (ACEI/ARB) are the first-line drugs for the treatment of essential hypertension (HTN), one of the most important risk factors for cardiovascular and cerebrovascular diseases. Intestinal flora and microbial metabolites have been demonstrated to play important roles in blood pressure (BP) regulation and HTN development. However, it remains elusive that the intestinal bacteria and metabolites associated with the protective effects of ACEI/ARB antihypertensive drugs against HTN. In this study, we evaluated the effect of ACEI/ARB on gut microbiome and metabolites in patients suffering HTN. We performed 16S rRNA sequencing and fecal metabolomic analysis of 36 HTN patients placed on ACEI/ARB therapy and 19 newly diagnosed HTN patients with no history of anti-hypertensive treatment. Patients under medication treatment were further classified into the well-controlled (n=24) and poor-controlled (n=12) groups according to their BP levels. ACEI/ARB improved the intestinal microbiome of HTN patients by reducing potentially pathogenic bacteria such as Enterobacter and Klebsiella, and increasing beneficial bacteria such as Odoribacter. Moreover, ACEI/ARB therapy was correlated with significant metabolomic changes in HTN patients, including progressively enhanced inositol from poor-controlled to well-controlled groups. The profiles of gut bacteria were linked to the production of metabolites, and the inositol was negatively correlated with Klebsiella, Enterobacter, and Proteobacteria. Our study suggests that ACEI/ARB modulates gut microbial composition and functions and alters microbial metabolites in HTN patients.